2021
DOI: 10.1177/01945998211019671
|View full text |Cite
|
Sign up to set email alerts
|

ERAS Protocols for Thyroid and Parathyroid Surgery: A Systematic Review and Meta‐analysis

Abstract: Objective Enhanced recovery after surgery (ERAS) protocols are evidenced-based multidisciplinary programs implemented in the perioperative setting to improve postoperative recovery and attenuate the surgical stress response. However, evidence on their effectiveness in thyroid and parathyroid surgery remains sparse. Therefore, our goal was to investigate the clinical benefits and cost-effectiveness of ERAS protocols for the perioperative management of thyroidectomy and parathyroidectomy. Data Source A systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Although recent interest in ERAS has led to a surge in studies demonstrating their efficacy in various adult surgical populations, [19][20][21] their use in pediatric patients is significantly more limited. The present study sought to synthesize the impact of ERAS protocol implementation across various centers following primary palatoplasty in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent interest in ERAS has led to a surge in studies demonstrating their efficacy in various adult surgical populations, [19][20][21] their use in pediatric patients is significantly more limited. The present study sought to synthesize the impact of ERAS protocol implementation across various centers following primary palatoplasty in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence supporting the safety and efficacy of the enhanced recovery after surgery concept for various procedures. The most recent meta-analysis showing beneficial effects are in thyroid surgery [8 ▪ ], aortic aneurysm surgery [9 ▪ ] and pediatric surgery [10 ▪ ] all supporting its benefits in shortening hospital stay and improving patients’ satisfaction.…”
Section: Enhanced Recovery After Surgery Pathwaysmentioning
confidence: 99%
“…In addition to ERAS protocols for head and neck cancer surgery, there is growing literature supporting the role of ERAS protocols for the perioperative management of thyroidectomy and parathyroidectomy. A recently published systematic review and meta‐analysis showed that ERAS protocols for thyroid and parathyroid surgery significantly reduced hospital LOS and costs without increasing complications or readmission rates 17 . In light of the benefits seen in patients with head and neck cancer and those undergoing thyroid and parathyroid surgery, we were interested in investigating the role of ERAS protocols for other patient populations in otolaryngology.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published systematic review and meta-analysis showed that ERAS protocols for thyroid and parathyroid surgery significantly reduced hospital LOS and costs without increasing complications or readmission rates. 17 In light of the benefits seen in patients with head and neck cancer and those undergoing thyroid and parathyroid surgery, we were interested in investigating the role of ERAS protocols for other patient populations in otolaryngology. Our objective therefore was to collate, critically appraise, and analyze the published literature regarding the use and efficacy of ERAS protocols for outpatient operations in otolaryngology.…”
Section: Introductionmentioning
confidence: 99%